(untitled) (Bangladesh Journal of Medical Microbiology, 2018)
Viral encephalitis remains a significant public health problem worldwide and one of the most important causes of mosquito borne viral encephalitis not only in Asia but all over the world. Its transmission is either from insect or environmental vectors or from human-to-human contact. It causes severe disease in humans, resulting in death or permanent neurologic deficits among the person who survives. As the risk of Japanese Encephalitis is persisting, implementation of strategies that will strengthen Japanese Encephalitis surveillance systems to understand the disease burden and apply vaccination protocols in national childhood immunization programs in Bangladesh. Bangladesh J Med Microbiol 2018; 12 (2): 21-23